What Price Better Health? : Hazards of the Research Imperative - Callahan, Daniel, 1930-2019 (Book collections on Project MUSE., 2003)
The idea that we have an unlimited moral imperative to pursue medical research is deeply rooted in American society and medicine. In this provocative work, Daniel Callahan exposes the ways in which such a seemingly high and humane ideal can be corrupted and distorted into a harmful practice.